Sosialisasi Energi Baru Terbarukan Untuk Pelajar SMP Annida Al Islamy Duri Kosambi, Cengkareng - Retno Aita Diantari (Terang, 2019)
Energy is a basic human need, which continues to increase in line with the level of life. Oil fuel / fossil energy is one of the nonrenewable energy sources which has been a mainstay to meet energy needs in all sectors of activity. The lack of students' understanding of the process of the occurrence of electrical energy makes them not much to save electricity in everyday life. During this time, most students in using electrical energy do not think about the impact on environmental sustainability. The activity of disseminating new and renewable energy is an effort or step taken to reduce dependence on fossil energy and simultaneously preserve the environment. This activity is a socialization activity led by STT-PLN lecturers to provide education to the public about the importance of understanding the use of electrical energy wisely in an effort to protect the environment.